Communication between neuronal somata and satellite glial cells in sensory ganglia - Huang, Li-Yen M. (2013)
Studies of the structural organization and functions of the cell body of a neuron (soma) and its surrounding satellite glial cells (SGCs) in sensory ganglia have led to the realization that SGCs actively participate in the information processing of sensory signals from afferent terminals to the spinal cord. SGCs use a variety ways to communicate with each other and with their enwrapped soma. Changes in this communication under injurious conditions often lead to abnormal pain conditions. “What are the mechanisms underlying the neuronal soma and SGC communication in sensory ganglia” and “how do tissue or nerve injuries affect the communication?” are the main questions addressed in this review.